PENGARUH FASILITAS, LOKASI, DAN HARGA TERHADAP KEPUTUSAN BERKUNJUNG KE OBJEK WISATA BUKIT KHAYANGAN KOTA SUNGAI PENUH - Elex Sarmigi; Ennike Parasmala (Institut Agama Islam Negeri Kerinci, 2021)
Purpose: The development of the world of tourism at this time has become one of the factors that boost the community's economy, therefore several factors need to be analyzed to obtain important information for tourism object managers in order to create value for visitors. The factors analyzed in this study are facilities, location, and price in shaping consumer behavior to visit the Bukit Khayangan tourist attraction, Sungai Penuh City. Design/Methodology/Approach: To get answers to the hypotheses formed, multiple regression analysis is carried out to answer the research objectives that have been prepared, namely by conducting t-test and F-test. Findings: From hypothesis testing, it is known that all independent variables in this study have a positive effect on the dependent variable, either partially or simultaneously. Research implications: From the results of this study, it is known that to attract consumers' interest in visiting a tourist attraction, it is necessary to have good facilities, location, and prices according to visitors (consumers).